MEMAHAMI REALITAS PEREMPUAN SEBAGAI SAKSI UNTUK TRANSAKSI NON - TUNAI MENURUT IBNU KATSIR DAN MUHAMMAD ABDUH - Umardani, Dwi (AL AMWAL (HUKUM EKONOMI SYARIAH), 2020)
This paper aims to find out the reality of woman's testimony for non-cash transactions. The method used in this paper is qualitative method with primary and secondary data collected through literature review and analyzed using comparative method. After comparing the opinions of the two leading commentators Ibn Kathir and Muhammad Abduh, after understanding the socio-cultural conditions especially the pattern of gender relations that occurred around the Arabian Peninsula both before and towards al-Qur'an was revealed, and after analyzing the opinions of the two interpreters contextually, the writer concludes that the provision of the requirement for the testimony of two women comparable to one man in QS 2: 282 is situational and temporal. Therefore, after socio-cultural conditions change, it is appropriate for woman's testimony to be positioned the same as man's testimony.